India in a changing global nuclear order - National Seminar on Nuclear Energy: India's Opportunities and Challenges (2005 : New Delhi, India); Gupta, Arvind, 1953-; Indian Pugwash Society; Institute for Defence Studies and Analyses (New Delhi : Published by Academic Foundation, in association with Indian Pugwash Society, 2009)
Papers presented at the National Seminar on Nuclear Energy: India's Opportunities and Challenges, held at New Delhi in November 2005.
section 1. Relevance of nuclear energy -- section 2. Perspectives on the Indo-US nuclear cooperation -- section 3. India and international non-proliferation efforts -- section 4. Conclusion -- section 5. Appendices.
"An IDSA, Indian Pugwash puclication".
Includes index.
Includes bibliographical references.
Keywords: Nuclear nonproliferation -- India -- Congresses; Nuclear energy -- Government policy -- India -- Congresses; India -- Foreign relations -- United States -- Congresses; United States -- Foreign relations -- India -- Congresses